Efektivitas OTT KPK Pasca Revisi UU KPK dalam Mengungkap Korupsi Sistemik di Pemerintahan Daerah: Studi Kasus Gubernur Riau - Hilaliah H (Media Hukum Indonesia (MHI), 2026)
This study analyzes the effectiveness of the Corruption Eradication Commission’s (KPK) Sting Operations (Operasi Tangkap Tangan/OTT) after the revision of Law Number 19 of 2019 on the KPK in uncovering systemic corruption in regional governments, using the OTT involving the Governor of Riau as a case study. The research employs a qualitative method with a case study approach through the analysis of legal documents and secondary data. The findings indicate that although OTTs remain effective as preliminary evidence in exposing systemic corruption, their implementation faces significant challenges following the amendment of the KPK Law, including restrictions on authority due to the supervisory board’s permit mechanism, changes in institutional status, and political as well as social complexities. The Riau Governor case study reveals systemic corruption patterns involving executive–legislative networks, the use of religious symbols for legitimacy, and resistance from political elites. The study recommends strengthening a progressive legal framework, optimizing the role of the Supervisory Board, adopting more integrative OTT strategies, and reforming regional governance to enhance the effectiveness of combating systemic corruption.